2019
DOI: 10.18639/rabm.2019.883878
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-inflammatory and Anti-apoptotic Role of Crocin against Expression of MMp-9, TIMP-1, MCP-1, Caspase-3, PPARα in Heart Tissue, and Metamorphoses of MicroRNA 188 in Hyperhomocysteinemic Rats

Abstract: Crocin (a water-soluble carotenoid) is the most abundant antioxidant among active constituents of Crocus sativus. Crocin has protective effects on brain, skeletal muscle, and kidney ischemia-reperfusion injury models via its antioxidant properties. The protective and anti-inflammatory effect of crocin against L-methionine-induced hyperhomocysteinemia (HHcy) in rats was evaluated. Thirty male albino rats were divided into three equal groups. Group I (control normal): rats fed ordinary diet without any treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In addition, it has been suggested that matrix MMPs activation plays a role in IS (Yang and Rosenberg, 2015) and amelioration of MMP-2 and MMP-9 expressions by CR may provide neuroprotection and protection of BBB functions under cerebral ischemia (Zhang et al, 2017b). The key inflammatory signaling molecules influenced by CR and related compounds include TNF-α, IL-1β, IL-1α, IL-6, IL-1, and MMP-9, monocyte chemoattractant protein-1 (MCP-1), macrophage inflammatory proten-1α (MIP-1α), vascular adhesion molecule-1 (VCAM-1), E-selectin and fractalkine (CX3CL1) and related signaling pathways namely NFκB, MAPK, TLR4, c-Jun N-terminal kinase (JNK), and P38 (Che et al, 2001;Hussein et al, 2019;Barthels and Das, 2020). In addition, autophagy is another important cellular mechanism involved in various cellular functions (Shen et al, 2021), and is a significant adaptive mechanism in IS (Ajoolabady et al, 2021).…”
Section: Potential Molecular Targetsmentioning
confidence: 99%
“…In addition, it has been suggested that matrix MMPs activation plays a role in IS (Yang and Rosenberg, 2015) and amelioration of MMP-2 and MMP-9 expressions by CR may provide neuroprotection and protection of BBB functions under cerebral ischemia (Zhang et al, 2017b). The key inflammatory signaling molecules influenced by CR and related compounds include TNF-α, IL-1β, IL-1α, IL-6, IL-1, and MMP-9, monocyte chemoattractant protein-1 (MCP-1), macrophage inflammatory proten-1α (MIP-1α), vascular adhesion molecule-1 (VCAM-1), E-selectin and fractalkine (CX3CL1) and related signaling pathways namely NFκB, MAPK, TLR4, c-Jun N-terminal kinase (JNK), and P38 (Che et al, 2001;Hussein et al, 2019;Barthels and Das, 2020). In addition, autophagy is another important cellular mechanism involved in various cellular functions (Shen et al, 2021), and is a significant adaptive mechanism in IS (Ajoolabady et al, 2021).…”
Section: Potential Molecular Targetsmentioning
confidence: 99%